Priority Directions of Development of Innovation Education Cluster in the Regional Agro-industrial Complex - Agarkova, Lyubov; Gurnovich, Tatyana; Filonich, Valentin; Shmatko, Sergei; Podkolzinaa, Irina (International Journal of Economics and Financial Issues, 2016)
Article is devoted to definition of a vector of development of an innovative and educational subsystem of agrarian and industrial complex of the region. Problems of integration interactions in system «Education – Science – Production» are investigated. The purpose of article is justification of recommendations about formation of multiplicative mechanisms of modernization of innovative and educational infrastructure of regional agrarian and industrial complex. The special attention is paid to questions of cluster reformatting of the scientific and educational sphere and innovative sphere on the basis of the numerical analysis of dependence between changes of parameters of development of branches of agrarian and industrial complex and the amounts of investments into the intellectual capital and technological innovations. As a result of the carried-out calculations the economic-mathematical models are received proving priorities of financing of cluster development of regional system of agrarian education. Application of system approach to research allowed to carry out differentiation on process productively sign of tools of development of an innovative and educational cluster of agrarian and industrial complex of the region. This aspect is supplemented also with consideration of possibility of acceleration of modernization processes due to generation of synergetic effects in block model on the basis of use of adaptable multiplicative mechanisms of ensuring system stability of an innovative and educational cluster. One of advantages of the offered model is the network form of representation of the mechanisms capable involved in its realization to transformations for practical use to plans of concrete actions and actions. Keywords: regional agrarian and industrial complex; innovative and educational cluster; multiplicative mechanism; network model. JEL Classifications: A2; I25; Q5